UPAYA INTEGRASI PENCEGAHAN PENYAKIT MENULAR PADA ANAK USIA DINI - Lelan Takaeb, Afrona Elisabeth; Ndun, Helga Nathalia Jilvera; Ndoen, Enjelita Mariance (P3M STIKES Aisyiyah Surakarta, 2019)
Communicable diseases are a serious threat in early childhood. Therefore, it is necessary to educate children as early as possible. This community service, which has been done in two Pre-schools, Viadolorosa and Kamboja, aimed to increase the behavior of students in preventing communicable diseases through intervention addressing predisposing, enabling and reinforcing factors. Intervention in predisposing factors was conducted through health education related to types of communicable diseases, prevention of communicable diseases and procedure of washing hands. Methods implemented were lecture, demonstration and singing and the media used included laptop, projector and visual teaching aid. Intervention in enabling factor was conducted thorough building a water container in each school as well as providing a package of health promotion kit. For reinforcing factor, intervention involved teachers, parents, and the head village as role models providing an example for students in practicing health behavior and as supervisors to help assess the impact of this project. As such, this integrated approach is expected to improve students? behavior in preventing communicable diseases earlier.